A Healthy Rhythm of Rest: Why a Sound Theology and Spiritual Praxis of Rest Matters to Life and Ministry - Richard Peck Woon (CARAKA: Jurnal Teologi Biblika dan Praktika, 2020)
Abstract. The article is for full-time Christian professionals to consider the importance of constructing a sound theology and spiritual praxis of rest in the context of life experience and practical ministry. It seeks to answer two critical questions from the perspective of the Sabbath, "What is the meaning of rest from a biblical perspective?" and "what is the role of rest in life and ministry". The intent is for ministers to value rest in the form of a sabbatical life that combines worship, work, and service within an essential relationship with God. A rhythm of rest is produced when our values and priorities are integrated into God's sovereign purpose. This is essential for the busy pastor who is actively engaging in ministry without enjoying God. If God is apparently absent in our relationship, then ministry loses its spiritual meaning and quality. It becomes a form of self-idolatry. A healthy faith restores our true rest.